Bridging Human–Computer Interaction and Natural Language Processing - Blodgett, Su Lin; Madaio, Michael; O’Connor, Brendan; Wallach, Hanna; Yang, Qian (EACL 2021 Workshop, 2021)
Welcome to the First Workshop on Bridging Human–Computer Interaction and Natural Language Processing! The rapid advancement of natural language processing (NLP) research has led to a variety of applications spanning a wide range of domains. As NLP applications are being used by more people in their everyday lives, and are increasingly powered by data generated by people, it is more important than ever that NLP researchers and practitioners adopt and develop methods to incorporate people into their work in meaningful ways. Perspectives from human–computer interaction (HCI) can enable NLP researchers and practitioners to advance the field of NLP in ways that are aligned with people’s needs, raising novel questions and research directions for both NLP and HCI. The workshop brings together researchers and practitioners from both disciplines to discuss shared research interests, highlight work at the intersection of these fields, and identify challenges and opportunities for productive interdisciplinary collaborations. We are delighted to present eighteen papers spanning reports of empirical work, research proposals, provocations, and surveys, along with seven non-archival papers to be presented at the workshop but not included in the proceedings. We would like to thank everyone who submitted their work to this workshop, as well as the program committee for their insightful feedback. We would also like to thank our invited speakers: Marti Hearst, Niloufar Salehi, and Burr Settles.